2018
DOI: 10.1172/jci92117
|View full text |Cite
|
Sign up to set email alerts
|

Reducing CXCR4-mediated nociceptor hyperexcitability reverses painful diabetic neuropathy

Abstract: Painful diabetic neuropathy (PDN) is an intractable complication of diabetes that affects 25% of patients. PDN is characterized by neuropathic pain and small-fiber degeneration, accompanied by dorsal root ganglion (DRG) nociceptor hyperexcitability and loss of their axons within the skin. The molecular mechanisms underlying DRG nociceptor hyperexcitability and small-fiber degeneration in PDN are unknown. We hypothesize that chemokine CXCL12/CXCR4 signaling is central to this mechanism, as we have shown that CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 97 publications
7
110
0
Order By: Relevance
“…In our results, the induction of mechanical allodynia did not completely correlate to the time course of macrophage accumulation. Nevertheless, the induction period is consistent with other reports using similar HFD feeding models (Jayaraj et al, 2018). These lines of evidence suggest that the molecular mechanisms of mechanical allodynia in the induction phase might be different from those in the maintenance phase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our results, the induction of mechanical allodynia did not completely correlate to the time course of macrophage accumulation. Nevertheless, the induction period is consistent with other reports using similar HFD feeding models (Jayaraj et al, 2018). These lines of evidence suggest that the molecular mechanisms of mechanical allodynia in the induction phase might be different from those in the maintenance phase.…”
Section: Discussionsupporting
confidence: 91%
“…Among the variety of basic approaches used to uncover the pathogenesis of complications in T2DM, high-fat diet (HFD)-induced diabetes with obesity has proved to be the most popular experimental model in rodents, being closely correlated with the known pathology of T2DM (Heydemann, 2016). For example, T2DM experimental rodent models induced by HFD feeding and patients with T2DM present hyperexcitability and spontaneous activity of primary sensory neurons reflecting the typical symptoms of neuropathic pain, such as hyperalgesia and allodynia (Baron et al, 2009;Menichella et al, 2014;Jayaraj et al, 2018). Therefore, HFD feeding is also a useful approach to investigate the molecular background of T2DM-related neuropathic pain in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies including ours have shown that Nav1.8 expressing neurons in the DRG play a critical role in the pathogenesis of WD-associated neuropathy 16,32 . To specifically test, the effect of WD or of saturated fatty acids on Nrg1 expressed in sensory neurons of the DRG, we directly purified mRNA in translation (associated with ribosomes) from DRG sensory neurons.…”
Section: Resultsmentioning
confidence: 57%
“…Others and we identified that WD-feeding led to peripheral neuropathy affecting the sensory neurons and their associated SC 16,32 . Previous reports demonstrated that modification in SC metabolism in the sciatic nerve were strongly linked to neuropathy phenotype in obesity 3 .…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation